Taking Close Others' Environmental Behavior Into Account When Striking the Moral Balance? Evidence for Vicarious Licensing, Not for Vicarious Cleansing. Issue 9 (November 2019) - Meijers, Marijn H. C.; Noordewier, Marret K.; Verlegh, Peeter W. J.; Zebregs, Simon; Smit, Edith G.
Research shows that people search for balance in their moral (e.g., environmentally friendly) behaviors such that they feel licensed to behave less morally after a previous moral act (licensing) and cleanse previous morally questionable behaviors by subsequently behaving more morally (cleansing). This article investigates whether this balancing may extend to close others, but not to nonclose others, and tests vicarious licensing and cleansing in the environmental domain. Study 1 showed that vicarious licensing effects are more likely when a close other displayed environmentally friendly (vs. neutral) behavior. Study 2 showed that environmental vicarious licensing effects are more likely for close than nonclose others. Studies 3 and 4 suggested that vicarious licensing effects, but not vicarious cleansing effects are more likely for close (vs. nonclose) others. Finally, a meta-analysis showed that overall these studies provide evidence for vicarious licensing effects, but not for vicarious cleansing effects in the environmental domain.